Adapting Arabic Language Learning Strategies to the Psychological Development of Madrasah Aliyah Adolescents: a Qualitative Exploratory Study - Astri Lupita Sari; Muhammad Nur Ihza; Siti Nurfitriani (UIN Sunan Gunung Djati Bandung, 2026)
This study explores the adaptation of Arabic language learning strategies tailored to the psychological development of adolescents at Madrasah Aliyah. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Data sources include teachers, students, and supporting documents such as lesson plans, syllabi, and textbooks. The analysis was conducted interactively through the stages of data reduction, data display, and conclusion drawing. The findings indicate that traditional strategies are less compatible with adolescents’ psychological needs, prompting teachers to implement adaptations through interactive methods, collaborative activities, digital media, and motivational reinforcement. Supporting factors for these adaptations include teacher motivation, student openness, and available facilities, while obstacles involve limited teacher competence, curriculum pressures, and inadequate resources. These adaptive strategies enhance students’ interest, participation, and self-confidence, and contribute to more humanistic and meaningful Arabic language learning.